2019
DOI: 10.1111/acel.13095
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐Dihydroxyvitamin D protects against age‐related osteoporosis by a novel VDR‐Ezh2‐p16 signal axis

Abstract: To determine whether 1,25-dihydroxyvitamin D (1,25(OH) 2 D) can exert an anti-osteoporosis role through anti-aging mechanisms, we analyzed the bone phenotype of mice with 1,25(OH) 2 D deficiency due to deletion of the enzyme, 25-hydroxyvitamin D 1α-hydroxylase, while on a rescue diet. 1,25(OH) 2 D deficiency accelerated age-related bone loss by activating the p16/p19 senescence signaling pathway, inhibiting osteoblastic bone formation, and stimulating osteoclastic bone resorption, osteocyte senescence, and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 55 publications
1
79
0
Order By: Relevance
“…Herein, A549 and SPC-A-1 cells were transfected with sh-NC and sh-LINC00301, respectively. Then, qPCR was conducted to examine the mRNA levels of EZH2 target suppressive genes [20,22,33,[36][37][38][39][40], including p15, p16, p21, p57, KLF2, PTEN, LATS2, RRAD, ASPP2, E-cadherin, and EAF2. The results demonstrated that the silence of LINC00301 remarkably increased the EAF2 mRNA level in both A549 and SPC-A-1 cells (Fig.…”
Section: Linc00301 Recruits Ezh2 and Mediates H3k27me3 At Eaf2 Promotmentioning
confidence: 99%
“…Herein, A549 and SPC-A-1 cells were transfected with sh-NC and sh-LINC00301, respectively. Then, qPCR was conducted to examine the mRNA levels of EZH2 target suppressive genes [20,22,33,[36][37][38][39][40], including p15, p16, p21, p57, KLF2, PTEN, LATS2, RRAD, ASPP2, E-cadherin, and EAF2. The results demonstrated that the silence of LINC00301 remarkably increased the EAF2 mRNA level in both A549 and SPC-A-1 cells (Fig.…”
Section: Linc00301 Recruits Ezh2 and Mediates H3k27me3 At Eaf2 Promotmentioning
confidence: 99%
“…Our previous studies, using homozygous knockout of 1α(OH)ase (Cyp27b1) (in 1α(OH)ase -/- mice) or double homozygous knockout of 1α(OH)ase and the parathyroid hormone gene ( Pth ) or double homozygous knockout of 1α(OH)ase and the calcium sensitive receptor gene ( Casr ), demonstrated that endogenous and exogenous 1,25(OH) 2 D could directly stimulate osteoblastic bone formation via the VDR 6 - 10 . Recently we further demonstrated that 1,25(OH) 2 D plays an anti-osteoporotic role via transcriptionally up-regulating expression of Bmi1 and Ezh2 in osseous cells via the VDR, subsequently, inhibiting oxidative stress and DNA damage, inactivating the p16 and p19 signaling pathways, inducing osseous cell senescence and SASP, facilitating osteoblastic bone formation, and inhibiting osteoclastic bone resorption 11 , 12 . These studies focused on long bone or vertebrae, however, the role and mechanism of 1,25(OH) 2 D in preventing mandibular bone loss 13 is less well investigated.…”
Section: Introductionmentioning
confidence: 96%
“…Interest in vitamin D research is reflected in nine articles in April and May of 2020 retrieved on PubMed (Sayers et al., 2020 ). Particularly, in those studies it was shown that 25(OH)D levels are lower in patients with positive PCR for SARS-CoV-2 (D’Avolio et al., 2020 ), that 1,25(OH) 2 D can protects against age-related osteoporosis (Yang et al., 2020 ), and that the hypovitaminosis D contributes to the sex-specific SARS-CoV-2 mortality (La Vignera et al., 2020 ). It was also pointed out that the levels of vitamin D might impact mortality from the SARS-CoV-2 infection (Marik et al., 2020 ), and that therefore vitamin D might play a role in the prevention of COVID-19 infection and mortality (Carter et al., 2020 ; Ilie et al., 2020 ; Jakovac, 2020 ).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%